Knockdown of GPR137 by RNAi inhibits pancreatic cancer cell growth and induces apoptosis. (24th August 2015) - Cui, Xianping; Liu, Yanguo; Wang, Bo; Xian, Guozhe; Liu, Xin; Tian, Xingsong; Qin, Chengkun
Abstract: G‐protein‐coupled receptors (GPCRs), the largest family of cell‐surface molecules involved in a number of biological and pathological processes, have recently emerged as key players in carcinogenesis and cancer progression. Orphan G protein‐coupled receptors (oGPCRs) are a group of proteins lacking endogenous ligands. GPR137, one of the novel oGPCR genes, was discovered by homology screening. However, the biological role of GPR137 in cancers has not yet been discussed and is of great therapeutic interest. In this study, we knocked down GPR137 via a lentivirus system in two human pancreatic cancer cell lines BXPC‐3 and PANC‐1. Knockdown of GPR137 strongly inhibited cell proliferation and colony formation. Flow cytometry showed that cell cycle was arrested in the sub‐G1 phase and apoptotic cells were significantly increased after GPR137 knockdown. Western blotting confirmed that GPR137 silencing induced apoptosis due to cleavage of PARP (poly ADP‐ribose polymerase) and upregulation of caspase 3. Furthermore, lentivirus‐mediated overexpression of GPR137 promoted the proliferation of PANC‐1 cells, suggesting GPR137 as a potential oncogene in pancreatic cancer cells. Taken together, our results prove the importance of GPR137 as a crucial regulator in controlling cancer cell growth and apoptosis.